The Development of Mitochondrial Gene Editing Tools and Their Possible Roles in Crop Improvement for Future Agriculture. Issue 1 (13th December 2021) - Yang, Jinghua; Yang, Xiaodong; Su, Tongbing; Hu, Zhongyuan; Zhang, Mingfang
Abstract: We are living in the era of genome editing. Nowadays, targeted editing of the plant nuclear DNA is prevalent in basic biological research and crop improvement since its first establishment a decade ago. However, achieving the same accomplishment for the plant mitochondrial genome has long been deemed impossible. Recently, the pioneer studies on editing plant mitogenome have been done using the mitochondria‐targeted transcription activator‐like effector nucleases (mitoTALENs) in rice, rapeseed, and Arabidopsis. It is well documented that mitochondria play essential roles in plant development and stress tolerance, particularly, in cytoplasmic male sterility widely used in production of hybrids. The success of mitochondrial genome editing enables studying the fundamentals of mitochondrial genome. Furthermore, mitochondrial RNA editing (mostly by nuclear‐encoded pentatricopeptide repeat (PPR) proteins) in a sequence‐specific manner can simultaneously change the production of translatable mitochondrial mRNA. Moreover, direct editing of the nuclear‐encoding mitochondria‐targeted factors required for plant mitochondrial genome dynamics and recombination may facilitate genetic manipulation of plant mitochondria. Here, the present state of knowledge on editing the plant mitochondrial genome is reviewed. Abstract : Mitochondria play essential roles in plant development and stress tolerance, particularly, in cytoplasmic male sterility widely used in production of hybrids. Precise editing of mitochondrial genomic DNA using the mitoTALENs, mitochondrial RNA editing mostly by nuclear‐encoded PPR proteins and editing of the nuclear‐encoding mitochondria‐targeted factors required for mitochondrial genome dynamics and recombination enable better understanding of the fundamentals of mitochondria.